2021
DOI: 10.3390/inorganics9040021
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of Multicompound TiO2/SiO2 Nanoparticles

Abstract: Multicompound TiO2/SiO2 nanoparticles with a diameter of 50–70 nm were generated using a liquid flame spray (LFS) nanoparticle deposition in a single flame. Here, we study the photocatalytic activity of deposited multicompound nanoparticles in gas-phase via oxidation of acetylene into carbon dioxide that gives new insight about the multicompound nanoparticle morphology. A small addition of SiO2 content of 0.5%, 1.0% and 3.0% significantly suppressed the photocatalytic activity by 33%, 44% and 70%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In 2021, Temerov et al synthesized TiO 2 NPs@SiO 2 (50–70 nm) using a liquid flame spray (LFS) deposition method in a single flame environment. 30 They studied the photocatalytic activity of deposited TiO 2 NPs@SiO 2 for oxidation of acetylene into carbon dioxide and they investigated the effect of the silica shell on the photocatalytic activity of these modified TiO 2 NPs. They reported that the catalytic activity was significantly suppressed when the SiO 2 content was increased to 0.5%, 1.0%, 3.0% and 5.0% (33%, 44%, 70% and 100% of suppression, respectively).…”
Section: Surface Modification Of Tio2npsmentioning
confidence: 99%
“…In 2021, Temerov et al synthesized TiO 2 NPs@SiO 2 (50–70 nm) using a liquid flame spray (LFS) deposition method in a single flame environment. 30 They studied the photocatalytic activity of deposited TiO 2 NPs@SiO 2 for oxidation of acetylene into carbon dioxide and they investigated the effect of the silica shell on the photocatalytic activity of these modified TiO 2 NPs. They reported that the catalytic activity was significantly suppressed when the SiO 2 content was increased to 0.5%, 1.0%, 3.0% and 5.0% (33%, 44%, 70% and 100% of suppression, respectively).…”
Section: Surface Modification Of Tio2npsmentioning
confidence: 99%
“…This could be avoided by incorporating silica (SiO 2 ) into the titania matrices [14,[23][24][25]. Silica insertion into the TiO 2 nanostructure not only increases the thermal stability of the highly photoactive anatase phase but also helps to prevent the mesoporous structure from collapsing [2,[26][27][28]. Introducing cellulose matrix as the second templating media to the triblock copolymer-TiO 2 -SiO 2 composite could further enhance the specific surface area and support the mesoporous structure with a higher degree of dispersibility in aqueous media that would enhance the photocatalytic efficiency [29].…”
Section: Introductionmentioning
confidence: 99%
“…[ 267–269 ] Leveraging the UCPL properties of CQDs, they can convert visible light to shorter wavelength light (325–425 nm) for the excitation of TiO 2 , thus exciting TiO 2 to generate additional electron/hole pairs for various photocatalytic reactions. This has been supported by improvements in photocurrent, photoelectric conversion efficiency, [ 270,271 ] and enhanced interfacial charge migration between CQDs and TiO 2 . [ 272,273 ]…”
Section: Applicationsmentioning
confidence: 99%